Spatial Econometric Model for Economics Development in Archipelago of Riau, as a Defense System Development in Republic of Indonesia - Susanti Linuwih; Setiawan Setiawan; Dwiatmono A. W Dwiatmono A. W; Wiryadi Wiryadi (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Province of Archipelago of Riau is a region in Indonesia which is adjacent to Singapore and Malaysia. This province has a great potential conditions diversity and natural resources. Planning on public prosperity improvement is necessary in order to increase loyalty and nationalism to Republic of Indonesia. The aim of this research is to build a spatial econometric model of economic growth in Province of Archipelago of Riau. One of the results shows that in recent 4 years Batam always gives the largest contribution to GRDP in Province of Archipelago of Riau. This can be understood that the contribution is more than 72.0% not only based on GRDP at current prices, but also based on GRDP at constant prices. Economic growth rate in regions in Province of Archipelago of Riau is higher than national economic growth rate. The model fits well because the coefficient of determination R2 is more than 85%. There are only 3 worse models, i.e. based on building construction in Batam (with R2= 59.6%), in Tanjungpinang (with R2=74.0%), and based on transportation and communication in Tanjungpinang (with R2=37.1%).